The Effects of the Free Trade Agreement with the United States and the Prices of Colombian Corn (2018)
Since the 1990s, Colombia has negotiated various free trade agreements with different countries and communities, eliminating import tariffs on different agricultural products that are sensitive to large volumes of importations, such as corn, a staple food in the family basket, which has shown a decrease in production in the last 20 years. This article proposes an evaluation of the effects of the Free Trade Agreement signed with the United States through the linear mixed model, having as a response variable the weekly prices of white and yellow corn marketed in the main Colombian market places in a period of time between June 1996 and December 2016, where there was a decrease in market prices, with repercussions on the incomes of Colombian corn producers.